Education management in knowledge based society - Daniela Todose (Contemporary Economics, 2008)
Europe is developing its knowledge society. It passes from an economy based on traditional factors of production (land, labor, capital) to one in which the major components are information and knowledge. It is well known that the socio-economical and technological development has an important impact on the labor market in developed nations. So, more skills are needed and a flexible and dynamic labor supply. Nowadays, developed and developing nations are increasingly able to deliver high skills at low costs.This paper investigates the achievements of the education systems and theinterdependences between education and welfare.
Keywords: 330